Education and Development in Bangladesh: A Study from Spatial Perspective (Journal of Bangladesh Institute of Planners, 2010)
Spatial polarization and geo-spatial inequality occur in case of development around the world. Importance of location and space for development is yet to receive attention in policy agenda of Bangladesh. This study is an attempt to assess the spatial variation in educational attainment and educational facilities at regional levels in Bangladesh. Regional variations in educational attainment have been assessed with respect to some selected indicators like literacy rate of 7 years and above, adult literacy rate, school enrolment rate, school attendance and student-teacher ratio. Relationship between poverty and educational attainment has also been assessed to find out the impact of poverty on education at regional levels in the country. In particular, this study has highlighted spatial variations in education facilities like number of primary school, secondary school, college through identifying developed and lagging regions in the country. Location Quotient (LQ) Analysis, Gini index, Composite Analysis have been used to identify the spatial variations in education at regional levels in the country. These findings may be helpful for government and policy makers to adopt necessary policies and strategies for education to ensure balanced development of the country at regional strata in Bangladesh.Journal of Bangladesh Institute of Planners, Vol. 3, Dec 2010, pp. 1-16